Buckling resistance, torque, and force generation during retreatment with D-RaCe, HyFlex Remover, and Mtwo retreatment files - Yoojin Kim; Seok Woo Chang; Soram Oh (Restorative Dentistry & Endodontics, 2023)
ObjectivesThis study compared the buckling resistance of 3 nickel-titanium (NiTi) retreatment file systems and the torque/force generated during retreatment.Materials and MethodsThe buckling resistance was compared among the D-RaCe (DR2), HyFlex Remover, and Mtwo R25/05 retreatment systems. J-shaped canals within resin blocks were prepared with ProTaper NEXT X3 and obturated by the single-cone technique with AH Plus. After 4 weeks, 4 mm of gutta-percha in the coronal aspect was removed with Gates-Glidden drills. Retreatment was then performed using DR1 (size 30, 10% taper) followed by DR2 (size 25, 4% taper), HyFlex Remover (size 30, 7% taper), or Mtrwo R25/05 (size 25, 5% taper) (15 specimens in each group). Further apical preparation was performed with WaveOne Gold Primary. The clockwise torque and upward force generated during retreatment were recorded. After retreatment, resin blocks were examined using stereomicroscopy, and the percentage of residual filling material in the canal area was calculated. Data were analyzed using 1-way analysis of variance with the Tukey test.ResultsThe HyFlex Remover files exhibited the greatest buckling resistance (p < 0.05), followed by the Mtwo R25/05. The HyFlex Remover and Mtwo R25/05 files generated the highest maximum clockwise torque and upward force, respectively (p < 0.05). The DR1 and DR2 files generated the least upward force and torque (p < 0.05). The percentage of residual filling material after retreatment was not significantly different between file systems (p > 0.05).ConclusionsNiTi retreatment instruments with higher buckling resistance generated greater clockwise torque and upward force.